Evaluation of Efficacy of Fungicides Against Fusarium oxysporum f. sp. lentis in Vitro at Lamjung, Nepal - Dahal, N.; Shrestha, R. K. (Journal of the Institute of Agriculture and Animal Science, 2018)
Fusarium is a soil borne pathogen which is common in almost all types of soil causing heavy losses in the crop production. Long term survival of pathogen in the soil as chlamydospores has increased its threat making it a highly devastating disease. High accessibility and simple application process of chemical control method has made it an effective and highly adopted approach of eliminating disease causing organisms. The present study was conducted in IAAS, Lamjung Campus to test the efficacy of fungicides in-vitro by poisoned food technique in PDA medium against Fusarium oxysporum f. sp. lentis. The fungicides tested were Carbendazim (50% WP), Chlorothalonil (75% WP) and Dithane M-45 (75% WP) at three different concentrations (100 ppm, 150 ppm and 200 ppm). The treatments were arranged in complete randomized design and replicated five times. The measurement of diameter of the fungal mycelium was taken 8 times at 48 hours interval until the fungus nearly covered the plate in control treatment and inhibition percent of the chemicals were calculated. All the fungicides inhibited the fungal growth significantly, among which carbendazim was highly effective in all the concentrations reducing 100% of mycelial growth followed by chlorothalonil. Dithane M-45 showed least inhibition i.e. 26.62% in 200 ppm (day 13). The chemicals exhibited increased tendency of inhibition with increased concentration.